Feasibility and Safety of Intercostal Cryoneurolysis During Pleuroscopy: A Novel Analgesic Approach Using a 1.7 mm Cryoprobe - Sammy Onyancha; Isabelle Dettmer; Njuxhersa Maloku; Gernot Rohde (Open Respiratory Archives)
Introduction: Pleuroscopy is a minimally invasive and highly effective procedure used for diagnosing pleural diseases. Despite its utility, pain during and after the procedure can be significant. Traditional analgesic approaches, including systemic opioids and local anaesthetics albeit potent, may provide incomplete pain relief and can be associated with side effects. Cryoneurolysis has emerged as a feasible analgesic technique in general surgery. However, an equivalent treatment modality has yet to be established for pleuroscopy. Objectives: To investigate the safety and feasibility of cryoneurolysis in pleuroscopy performed using a 1.7 mm cryoprobe via a semi-rigid pleuroscope. Materials and methods: We conducted a prospective, single-centre observational study on 43 patients who underwent pleuroscopy at our institution between January 2024 and December 2024, of which 25 received cryoneurolysis. Pain levels were assessed using a Numeric Rating Scale (NRS) immediately post-procedure and at 24 and 72 h. Complications and long-term adverse events were documented. Results: NRS scores after cryoneurolysis showed successful pain management both immediately post-procedure (mean NRS: 3.1) and at subsequent time points (24 h: 2.0; 72 h: 1.5). No major complications, such as major haemorrhage or nerve injury leading to persistent deficits, were observed. Minor complications occurred in 2 patients, who experienced a transient numbness immediately post-procedure. Analgesic requirements were lower than the control group, with 68% of patients requiring only mild oral analgesics post-procedurally. Conclusion: The use of cryoneurolysis during pleuroscopy appears to be a feasible, safe, and effective technique for pain management. However, further studies with larger cohorts are warranted to validate the findings. Resumen: Introducción: La pleuroscopia es una técnica mínimamente invasiva y muy eficaz para el diagnóstico de las enfermedades pleurales. A pesar de su utilidad, no obstante, se asocia con dolor significativo durante y después del procedimiento. Las técnicas de analgesia tradicionales, como los opiáceos sistémicos y los anestésicos locales, aun siendo potentes, no siempre comportan un alivio completo del dolor y pueden producir efectos secundarios. La crioneurólisis ya es una técnica analgésica viable en cirugía general, pero todavía es preciso fijar una modalidad terapéutica equivalente para la pleuroscopia. Objetivos: Estudiar la seguridad y la viabilidad de la crioneurólisis en la pleuroscopia, realizada con una criosonda de 1,7 mm por medio de un pleuroscopio semirrígido. Materiales y métodos: Realizamos un estudio observacional prospectivo y unicéntrico con 43 pacientes sometidos a pleuroscopia en nuestro hospital, entre enero y diciembre de 2024, a 25 de los cuales se les practicó la crioneurólisis. Se evaluaron los niveles de dolor con una escala numérica, inmediatamente después de la intervención y a las 24 y 72 horas. Se documentaron las complicaciones y los acontecimientos adversos a largo plazo. Resultados: Las puntuaciones de la escala numérica indican que el control del dolor fue efectivo tanto inmediatamente después de la crioneurólisis (puntuación media: 3,1) como en los momentos posteriores (24 horas: 2,0; y 72 horas: 1,5). No se observaron complicaciones importantes, como hemorragias graves o lesiones nerviosas asociadas a déficits persistentes. Tuvieron complicaciones leves dos pacientes, quienes refirieron un entumecimiento pasajero inmediatamente después de la intervención. Los requisitos de analgesia fueron más bajos que en el grupo de control: después de la intervención, el 68% de los pacientes solo necesitaron analgesia oral ligera. Conclusión: La crioneurólisis representa una técnica factible, segura y eficaz para controlar el dolor durante la pleuroscopia. Con todo, habrá que validar estos resultados en estudios con cohortes más grandes.